HUBUNGAN TINGKAT STRES DAN PERILAKU MEROKOK PADA REMAJA LAKI LAKI SMA MALANG - Deki sipul, Mikael Umbu (STIKES Widyagama Husada, 2025)
Smoking behavior is a serious health problem, especially among adolescents. Cigarettes contain addictive substances like nicotine, which can cause dependence and various chronic diseases. Stress is a factor that can trigger smoking behavior in adolescents as smoking is often perceived as a way to relieve or escape from stress.To examine the correlation between stress and smoking behavior in male adolescents in grade XII at SMA Malang.This study uses a quantitative design with a descriptive correlational approach and a cross-sectional design. The sample consists of 53 respondents, selected using purposive sampling. Data were collected using the Perceived Stress Scale (PSS) questionnaire and a smoking behavior questionnaire. Data analysis was performed using Somers'D statistical test.The statistical test results showed a p-value of 0.000 (below 0.005) and an r value of 0.845, indicating a strong and significant correlation between the two variables.There is a relationship between stress levels and smoking behavior in male adolescents at SMA Malang.